Survey of Youths in Custody, 1987: (United States) ([Verlag nicht ermittelbar], 1989)
This data collection, the first survey of youths confined to long-term, state-operated institutions, was undertaken to complement existing Children in Custody censuses. It also serves as a companion to the Surveys of State Prisons, allowing comparisons between adult and juvenile populations. The survey provides detailed information on the characteristics of youths held primarily in secure settings within the juvenile justice system. The data contain information on criminal histories, family situations, drug and alcohol use, and peer group activities. For youths committed for violent acts, data are available on the victims of their crimes and on weapon use.